Многообразие как проблема образовательного менеджмента - Шерайзина, Роза Моисеевна; ДмитриевнаЗиновьева, Светлана (International Dialogues on Education Journal, 2016)
The article discusses and justifies the priorities of the Department of Vocational Pedagogical Education and Social Management at the Federal State-Funded Novgorod State University, by addressing diversity issues in the preparation of master’s degrees in educational management. Not only is the diversity of contemporary educational organization explicated,but also the variety of competencies among master’s-degree graduates, as well as the criteria and requirements for this multilevel system of governance. Priority areas include: the development of international project activity in educational programs and technologies, the creation of a communicative learning environment, a social and active department.